Knowledge, attitude and practices of hand hygiene among nurses and nursing students in a tertiary health care center of Central India: a questionnaire based study - Mehta, Abhishek; Tripathi, Kiran (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care associated infections and emerging multi drug resistance in nosocomial pathogens is perceived as a serious public health threat with grievous concerns. Hand hygiene if practiced properly is cheapest, simplest and most effective tool in tackling this problem. The objective of this study was conducted to assess levels of knowledge, attitude and practice in various aspects of hand hygiene in nurses and nursing students in the study area for identifying gaps for planning necessary corrective measures. Methods: A cross sectional study involving self-administered pre-structured anonymous questionnaires administered to 50 staff nurses and 80 nursing students posted at a tertiary health care center of Central India. Z test of proportions was used to compare the percentages for each of the appropriate responses between the two study groups. Results: Most of the study participants exhibited moderate levels of knowledge and practice with marginal difference between two study groups. While nursing students were found to exhibit a remarkably higher level of attitude than staff nurses, difference being statistically significant. Conclusions: This study stresses upon the growing need for prompt interventions at institutional level for addressing the gaps evident from the study.